A study on cyberbullying among visually impaired youth in Malaysia: prevalence and its associated factors - Ku, Wen Li (2024)
Technological advances have revolutionised the way we communicate, especially with the influx of social networking sites used primarily by young people. However, a worldwide phenomenon, cyberbullying, is a cause of concern for youth advocates who are up to date with technology. Malaysian visually impaired youth are vulnerable to cyberbullying, but the aspect has been poorly studied in Malaysia. This is a mixed method sequential study with two phases. Phase 1 uses quantitative methods to investigate the prevalence rate of cyberbullying from the perspectives of victims, perpetrators, and bystanders among Malaysian visually impaired youth as well as the technological exposure, self-efficacy, and social support associated with cyberbullying experiences and if social support acted as a mediator between variables. For Phase 2, qualitative focus groups were used to collect data on how participants experience cyberbullying with regards technological exposure, self-efficacy, and social support. 199 Malaysian visually impaired youths (Mean = 17.81; S.D.= 1.641) participated in this mixed-method cross-sectional study (Phase 1) with Braille paper-and-pen and voice-over online surveys. Data were analysed using the Statistical Package for the Social Sciences (SPSS) and Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed research hypotheses. For phase 1, the results revealed that of the 188 participants, 47.2% are cybervictims, 10.6% are cyberperpetrators, and 50.3% are cyberbystanders. Social support from teachers is the most important factor negatively influencing cyberbullying experiences, followed by empathic and defending self-efficacy. Results also showed that defending self-efficacy was positively related to social support from family and friends and social support from teachers. Indirect mediating relationships were investigated and found that social support from teachers mediated the relationship between defending self-efficacy and cyberbullying experiences, as well as empathic self-efficacy and cyberbullying experiences. For Phase 2, the research objective was to explore how participants experience cyberbullying with regards technological exposure, self-efficacy, and social support and data were analysed using NVivo software. Phase 2 qualitative findings supported the quantitative results and provided the rich details in the three themes which emerged: (1) Technological exposure, (2) Self-efficacy, and (3) Social support. To raise awareness of cyberbullying, an educational programme can be considered that focuses on raising awareness of cyberbystanders. Implementing educational programmes on the importance of support from school counsellors and teachers should be considered to teach students skills such as coping mechanisms for cyberbullying to reduce the incidence of cyberbullying. In addition, implementation of law and regulation by the government is relatively important and should be drawn attention to, in order to decrease the likelihood of cyberbullying incidents.